Peak-end pizza: prices delay evaluations of quality - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2015)
Purpose - The purpose of this paper is to determine if the level of payment required for consumption changed the relationship between a consumer's overall evaluation of a hedonic consumption experience and the evaluation of first, middle, last piece and peak consumption experiences. Design/methodology/approach - Diners at an all-you-can-eat restaurant were either charged $ 4 or $ 8 for an Italian lunch buffet. Their taste, satisfaction and enjoyment evaluation of each piece of pizza they had was taken along with other measures of behavior and self-perceptions. Using regression analysis, we examine the relationship between these single event evaluations and their overall evaluations of the experience. Findings - For the diners who paid $ 4 for their buffet, overall taste, satisfaction and enjoyment evaluation depend on the taste of the last piece of the pizza and the peak taste consistent with prior findings. For those paying $ 8 for the buffet, the first piece of pizza is more important in predicting the overall taste, satisfaction and enjoyment ratings. Practical implications - Consumers do not evaluate their meal experience based on every moment of their experience. Rather, just a few moments appear to impact overall evaluation. Firms that sell access to a series of experiences, such as an all-you-can-eat buffet, should focus on leading customers to the best experience first particularly when prices may be considered moderate to high. Originality/value - In this paper, we seek to unravel the relationship between price paid and the peak-end heuristic by examining the importance of peak and end experiences under two different pricing regimes. Our study also indicates that the peak-end rule may depend on specific contextual factors.
Keywords: Pricing; Enjoyment; Consumer satisfaction; Hedonic consumption experience; Peak-end rule; Taste evaluation; RETROSPECTIVE EVALUATIONS; DURATION NEGLECT; PRODUCT QUALITY; SATISFACTION; DISCONFIRMATION; DETERMINANTS; MEMORIES; UTILITY; PAIN; LESS